Analisis Emergency Response Plan (ERP) Kegiatan Praktek Terbang Taruna Jurusan Penerbang Sekolah Tinggi Penerbangan Indonesia Curug - Tri Saputra, Surya (Langit Biru: Jurnal Ilmiah Aviasi, 2021)
The practice of flying is an activity that has a high potential risk of causing negative impacts, such as loss of material, human life and reputation of an agency. When these risks cannot be avoided, an Emergency Response Plan (ERP) is needed as an organizational guide for dealing with emergency situations. This study, which was conducted in 2017, aims to analyze the Emergency Response Plan (ERP) guidelines, especially in the implementation of cadets' flying practices in the Aviation Department – Indonesian Civil Aviation Institute Curug. In this study, the authors used the gap analysis method to determine the gap between ideal conditions and existing conditions based on Doc. 9859 Safety Management Manual. The stages in this research are conducting a literature study, making gap analysis, identifying and assessing potential risks that may occur and conducting a review and validation of documents. This study concludes that the Emergency Response Plan (ERP) Manual is required to be refined and an emergency handling simulation is needed.